Co3O4 Catalysts on CeO2-ZrO2 Supports and Co3O4-CeO2 Catalysts on Al2O3/SiO2 Supports for the Oxidation of Propylene. (15th March 2015) - Nguyen, Tien The; Pham, Phuong Thi Mai; Le, Thang Minh; Van Driessche, Isabel
Abstract : Different compositions of Co3 O4 catalysts on CeO2 -ZrO2 solid solution (Ce0.9 Zr0.1 O2 and Ce0.8 Zr0.2 O2 ) have been studied for the oxidation of propylene. The optional amount of Co3 O4 active phase on CeO2 -ZrO2 support of 30 wt% was found. The mixed Co3 O4 -CeO2 -ZrO2 with the same composition of the optimal supported ones showed approximately the same activity, which was not higher than the activity of the mixed Co3 O4 -CeO2 catalyst. Catalytic activities of mixed Co3 O4 -CeO2 with different loading contents supported on high surface area supports (Al2 O3, SiO2 ) were then measured. The optimal composition of active phase was still 30 wt% but the minimum temperature of the highest activity increased to above 300°C due to the inert nature influence of the support.